Structure and wear resistance of TiN and TiAlN coatings on AZ91 alloy deposited by multi-arc ion plating - 赵晖 王晓辉 刘秋雷 陈立佳 刘正 (Transactions of Nonferrous Metals Society of China, 2010)
In order to investigate the microstructure of TiN and TiAlN coatings and their effect on the wear resistance of Mg alloy, TiN and TiAlN coatings were deposited on AZ91 magnesium alloy by multi-arc ion plating technology.TiN and Ti70Al30N coatings were prepared on the substrate,respectively,which exhibited dark golden color and compact microstructure.The microstructures of TiN and Ti70Al30N coatings were investigated by X-ray diffractometry（XRD）and scanning electron microscopy（SEM）.The micro-hardness and wear resistance of TiN and Ti70Al30N coatings were investigated in comparison with the uncoated AZ91 alloy. The XRD peaks assigned to TiN and TiAlN phases are found.The hardness of TiN coatings is two times as high as that of AZ91 alloy, and Ti70Al30N coating exhibits the highest hardness.The wear resistance of the hard coatings increases obviously as result of their high hardness.